Evapotranspiration and Its Energy Exchange in Alpine Meadow Ecosystem on the Qinghai-Tibetan Plateau - Jie LI; Sha JIANG; Bin WANG; Wei-wei JIANG; Yan-hong TANG; Ming-yuan DU; Song GU (Journal of Integrative Agriculture, 2013)
To understand the water and energy exchange on the Qinghai-Tibetan Plateau, we explored the characteristics of evapotranspiration (ET) and energy fluxes from 2002 to 2005 over a Kobresia meadow ecosystem using the eddy covariance method. The ratio of annual ET to precipitation (P) of meadow ecosystem was about 60%, but varied greatly with the change of season from summer to winter. The annual ET/P in meadow was lower than that in shrub, steppe and wetland ecosystems of this plateau. The incident solar radiation (Rs) received by the meadow was obviously higher than that of lowland in the same latitude; however the ratio of net radiation (Rn) to Rs with average annual value of 0.44 was significantly lower than that in the same latitude. The average annual ET was about 390 mm for 2002-2005, of which more than 80% occurred in growing season from May to September. The energy consumed on the ET was about 44% of net radiation in growing season, which was lower than that of shrub, steppe and wetland on this plateau. This study demonstrates that the Kobresia meadow may prevent the excessive water loss through evapotranspiration from the ecosystem into the atmosphere in comparison to the shrub, steppe and wetland ecosystems of the Qinghai-Tibetan Plateau.